Pemberdayaan Masyarakat Desa Plesungan Melalui Penyuluhan Pembuatan Oleh-Oleh Makanan dan Cenderamata Khas Desa - Luqman Al Hakim; Siti Supeni; Mohammad Khabibullah; Yudha Skenoma (Politeknik Harapan Bersama, 2021)
The impact of the covid-19 pandemic on society has occurred in almost all sectors and regions of Indonesia, even the world. One of them is regarding the productivity of the community which has begun to decline due to the reduction in employees. In addition, the limited expertise possessed by rural communities cannot yet be compared with those in remote cities. One of the efforts to overcome this problem is to hold outreach and counselling in the framework of the Community Empowerment Program carried out by the UNISRI KKN-PPM Team in Plesungan Village, Gondangrejo District, Karanganyar Regency, Central Java Province in 2020 by empowering Communities affected by the Covid-19 pandemic and mothers. PKK and in order to prepare Plesungan Village as a tourism village through a program of making souvenirs of food and souvenirs typical of Plesungan Village by utilizing local wisdom such as cassava (pohong), corn, kencur which is processed into typical village food, and the use of used candles, leaves, flowers wild or ornamental dried as a souvenir. This is as motivation and support for the community to be able to compete with other products, so entrepreneurship counseling and packaging are given. The result of this activity is the manufacture of food souvenirs and souvenirs typical of the village in the form of Cassava Bolu, Herbal Kencur, Egg Corn, Aromatherapy Candles, and also resin key chains.